Characterizing the vitamin and mineral status of farmed American bison in the United States - Okoren, Claire, author; Edwards-Callaway, Lily, advisor; Engle, Terry, advisor; Torres-Henderson, Camille, committee member (Colorado State University. Libraries, 2025)
The American bison (Bison bison) has become increasingly prevalent within the agricultural sector, yet limited research exists on their specific nutritional needs, particularly for vitamins and minerals. Minerals play a critical role in physiological processes like muscle development, reproduction, and enzyme activation, while vitamins act as coenzymes essential for metabolic pathways and immune functions. This study aimed to establish baseline mineral and vitamin concentrations in farmed American bison tissues and to analyze mineral and vitamin contents of feed and water across locations within the United States. Post-mortem samples, including blood, liver, kidney, and muscle, were collected from bison processed at USDA-inspected facilities. Seasonal sampling captured variations in feed and water composition. Tissue samples underwent mineral analysis using inductively coupled plasma-optical emission spectrometry (ICP-OES), while vitamin levels were determined via liquid chromatography-tandem mass spectrometry (LC-MS/MS). To provide context, a scoping review of existing literature on mineral and vitamin concentrations in bison and related species was conducted, yielding weighted means for comparison. Results highlight the nutritional variability across ranches, seasons, ages, and sexes offering foundational data for developing species-specific dietary recommendations. These findings address a critical knowledge gap in farmed American bison mineral and vitamin status, and hopes to drive future research in bison agriculture, enhancing animal health, welfare, and productivity in these farmed settings.
Keywords: mineral; status; bison; vitamin; nutrition